Entrepreneurship and Disruption Innovation for Sustainable Economic Development - (PhD), Ihuoma Ikemba Efughi (Covenant Journal of Entrepreneurship, 2019)
This paper which is based on systematic review of literature examines the concept of entrepreneurship and disruptive innovation as crucial factors that drive the economic growth and development of a nation. Several literatures on entrepreneurship and economic development have shown how entrepreneurship has decreased the level of poverty and improved the standard of living of some transition or emerging countries. This paper however argues that, it is not all forms of entrepreneurship that bring about changes in terms of restructuring and the diversification of economies for sustainable economic development. The paper compares disruptive innovation with Schumpeter’s theory of ‘creative destruction’ economic miracle for the restructuring of poor economies. The paper recognizes the role of knowledge- based entrepreneurial firms or start-ups in the introduction of new products, services, processes and innovation and the challenges faced by these firms, which stand as barriers to disruptive innovation.